Research progress of single nucleotide polymorphisms and immune cells in diabetic kidney disease - GUO Meng-ran, MIN Hang, YE Yue, XU Xiao-shuang, ZHEN Dong-hu (Jichu yixue yu linchuang, 2022)
Diabetic kidney disease has obvious family aggregation and ethnic differences, some single nucleotide polymorphisms (SNPs) related to the susceptibility of diabetic kidney disease have been identified, especially engulfment and cell motility 1 (ELMO1) and solute carrier family 12 member 3(SLC12A3), which are related to the development of diabetic kidney disease in Chinese population. Meanwhile, inflammation plays a key role in the occurrence and development of diabetic kidney disease, including T cell and type-2 innate lymphoid cell(ILC2) promote chronic inflammatory response and fibrosis of kidney by secreting inflammatory factors.